Analisis Faktor pada Kinerja Keuangan dan Mediasi Struktur Modal pada Komite Audit di Perusahaan Property - Tri Indah Sri Mulyaningsih (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Financial performance evaluates how successful the company has achieved business activities. The purpose of this research is to analyze if financial performance (ROA) affected by firm size, investment opportunity set (IOS), dividend (DPR), audit committee, and capital structure (DAR). Also the mediation effect of capital structure in the audit committee to financial performance. Population in this research is 56 property sector companies on BEI (www.idx.co.id). The sample in this research is 28 property companies (period 2014-2018) chosen by purposive sampling. This study uses a type of conclusive causal. The data analysis technique used path analysis with IBM SPSS 20. The results show that IOS has a significant effect on financial performance. Firm size, dividend & capital structure has a significant negative effect on financial performance. The audit committee does not significant to financial performance and capital structure (DAR). And also capital structure (DAR) does not mediate the audit committee to financial performance.